Gendered mobility strategies and challenges to sustainable travel—patriarchal norms controlling women's everyday transportation - Christina Lindkvist; Christina Lindkvist; Christina Lindkvist (Frontiers in Sustainable Cities, 2024)
Sweden is a country with an international reputation for gender equality. The political goal of gender equality is based on feminist analysis of what constitutes a just society according to gender and the fight against patriarchal norms. Despite policy recommendations and legislation that counteract discrimination against women, women still fear traveling by public transport and being out in the evenings. This indicates that Swedish society still has patriarchal norms to deal with. The article is based on qualitative interviews and data retrieved from the Swedish National Statistics, SCB. The interviews explored mobility practices and strategies, experiences with different modes of transport, and reliability, affordability, and comfort of the mobility options available. The results shows that travel choices for women are affected by their concerns about safety and related necessary adaptation to situations identified as threatening. Despite the “mythical mantra” of the gender equal society, Sweden share the patriarchal norms with other countries, that delimits women's use and access to public space and public transport.